2012
DOI: 10.1002/btpr.1507
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electroporation in plant tissues via low frequency pulsed electric fields: Influence of cytoplasmic streaming

Abstract: Pulsed electric fields (PEF) are known to be effective at permeabilizing plant tissues. Prior research has demonstrated that lower pulse frequencies induce higher rates of permeabilization, but the underlying reason for this response is unclear. Intriguingly, recent microscopic observations with onion tissues have also revealed a correlation between PEF frequency and the subsequent speed of intracellular convective motion, i.e., cytoplasmic streaming. In this paper, we investigate the effect of cytoplasmic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…() reported a strong correlation between the persistence of cytoplasmic streaming and overall damage to the tissue as a function of frequency in onion tissue. The high net yield of extracted carotenoids after PEF treatment at 5 Hz in the current study might be due to the persistence of cytoplasmic streaming during low PEF frequency, which plays an important role in accelerating the physical damage of cell membranes (Asavasanti et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…() reported a strong correlation between the persistence of cytoplasmic streaming and overall damage to the tissue as a function of frequency in onion tissue. The high net yield of extracted carotenoids after PEF treatment at 5 Hz in the current study might be due to the persistence of cytoplasmic streaming during low PEF frequency, which plays an important role in accelerating the physical damage of cell membranes (Asavasanti et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the effect of PEF treatment on carotenoid extractability was compared with the untreated samples from the same batch. There is a critical frequency of ~1 Hz below which permeabilisation of onion tissue was reported to be significantly increased (Asavasanti et al ., ). These authors reported a correlation between PEF frequency and the subsequent speed of intracellular convective motion, that is, cytoplasmic streaming.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study where a 50Hz oscillating electrical field was imposed on plant tissue, permeabilisation of the tissue was brought about in a manner dependent upon the presence of actin, suggesting that actin fila ment oscillation and/or cytoplasmic streaming may be allow the opening of the plasma membrane, 203 which possibly may allow the initiation of APs.…”
Section: Does Orch or Apply To Plants And If So Could Plants Be Conmentioning
confidence: 98%
“…PEF treatment at a low frequency can increase the rate of tissue permeabilization. 20 At low frequencies, the GT cell membrane acts as a capacitor to prevent the flow of electrical current into the intracellular medium. After increasing the frequency, the cell membrane becomes less and less resistant to current flow.…”
Section: Influence Of Frequency On Gt Cell Breakagementioning
confidence: 99%